The sustainable management of vertisols - Syers, John K. (John Keith); Penning de Vries, F. W. T.; Nyamudeza, Phibion (IBSRAM proceedings ;, 2001)
This book provides an up-to-date information on Vertisols research, and guides readers to important reference material. Four keynote papers and eight country papers and national perspectives on the management of Vertisols in Malawi, South Africa, Sudan, Tanzania, Zambia, Zimbabwe, Ghana and Ethiopia are presented. International perspectives on the management of (Vertisols in India, Australia and Texas, USA) are also discussed.